SS-RBAC: Secure Query Processing Model for Semantic Sensor Networks - Jeong, Dongwon; Jeong, Hyejin; Jeong, Young-Sik (International Journal of Advanced Science and Technology, 2017)
This paper proposes a novel secure query processing model for semantic sensor networks. A semantic sensor network (SSN) is a sensor network which includes semantics of sensory data and context information, and relationships between the semantics. In brief, SSN is an extension of the current Sensor Network (SN) and realized by using Semantic Web (SW) technologies. Although various researches have been activated on SSN, there is little activity on how to access data in semantic sensor networks in safe. This paper proposes a new access control model for secure query processing under semantic sensor networks. The proposed security model is based on RBAC (Role-Based Access Control) and enables secure access control of ontology for SSNs.